Elemental composition of Camelina Sativa (L.) Crantz - Lisova, T. O.; Trzhetsynskyi, S. D.; Лісова, Тетяна Олександрівна; Тржецинський, Сергій Дмитрович (My University, 2022)
The aim of the work is to establish the qualitative composition and quantitative content of mineral elements in the herb of Camelina sativa (L.) Crantz. Materials and methods. Camelina sativa (L.) Crantz herb («Slavutych» species) was selected as the object of the study. Samples of seeds for cultivation were provided by the National Center for Plant Genetic Resources of Ukraine. To determine the qualitative composition and quantitative content of macro- and microelements, an atomic emission spectrograph method with photographic registration on the DFS-8 device was used. Results and discussion. The obtained experimental data of the macro- and micronutrient composition of Camelina sativa (L.) Crantz herb indicate the presence of at least 19 elements in the raw material, of which 6 are macroelements, 8 are microelements and 5 are ultra-microelements. Macroelements such as K, Ca, and Mg are accumulated in the largest quantities; microelements such as Al, Fe, Zn, and Mn are accumulated in the largest quantities. The content of inorganic elements of toxicological significance does not exceed in raw materials the maximum allowable concentrations set by the standards. K, P, and Ca have the highest coefficient of biological accumulation. Of particular interest are Zn and Mg, which may have a variety of pharmacological effects in the treatment of metabolic syndrome and diabetes. Zn is known to play an important role in the activity of the pancreas, insulin synthesis and its binding to hepatocytes, as well as in lipoprotein synthesis. Mg restores insulin sensitivity, thereby preventing the formation of insulin resistance. Conclusions. The elemental composition of Camelina sativa herb was first studied with atomic emission spectrometry. The obtained data enable to predict certain types of pharmacological activity of extracts and substances obtained from Camelina sativa herb and will be used in the development of quality control methods for raw materials. Мета роботи. Встановлення якісного складу та кількісного вмісту мінеральних елементів в траві рижію посівного. Матеріали та методи. Об’єктом дослідження було обрано траву рижію посівного сорту «Славутич». Зразки насіння для вирощування були надані Національним центром генетичних ресурсів рослин України. Для визначення якісного складу та кількісного вмісту макро- та мікроелементів використовували метод атомно-емісійної спектрографії з фотографічною реєстрацією на приладі ДФС-8. Результати та їх обговорення. Отримані експериментальні дані щодо макро- та мікроелементного складу трави рижію посівного свідчать про наявність в сировині не менше 19 елементів, із яких 6 відноситься до макроелементів, 8 мікроелементів 5 ультрамікроелементи. У найбільших кількостях акумулювались такі макроелементи як калій, кальцій, маґній; мікроелементи – алюміній, ферум, цинк, манґан. Вміст неорганічних елементів у сировині, які мають токсикологічне значення не перевищують гранично допустимі концентрації, що встановлені стандартами. Найвищі показники коефіцієнту біологічного накопичення були для калію, фосфору та кальцію. Певний інтерес представляють цинк та маґній, які можуть проявляти різноманітні фармакологічні ефекти при лікуванні метаболічного синдрому та цукрового діабету.Відомо, що цинк відіграє важливу роль у діяльності підшлункової залози, синтезі інсуліну та процесах його зв’язування з гепатоцитами, синтезі ліпопротеїнів. Маґній відновлює чутливість до інсуліну, перешкоджаючи тим самим формуванню інсулінорезитентності. Висновки. Методом атомно-емісійної спектрометрії вперше досліджено елементний склад трави рижію посівного. Отримані дані дають змогу прогнозувати певні види фармакологічної активності екстрактів і субстанцій, одержаних з трави рижію посівного, та будуть використані при розробці методик контролю якості на сировину.
Елементний склад трави рижію посівного Camelina sativa (L.) Crantz
Лісова Т. О. - ORCID: 0000-0001-6976-8630; Тржецинський С. Д. - ORCID: 0000-0002-5219-3313.
Keywords: Camelina sativa (L.) Crantz; herb; elemental composition; atomic-emission spectrography; рижій посівний; трава; елементний склад; атомно-емісійна спектрографія